Tugas Polisi dalam Upaya Perlindungan Hak Asasi Manusia dan Penegakan Hukum - DPM Sitompul (Fakultas Hukum Universitas Islam Indonesia, 2003)
In the effort of Human right enforcement always deals with the task of police and law, because Human Right needs law instrument and the enforcement process by the police for granting the existence In the actual life. Without Instrument of law, Human Right finds the difficulties in enforcing by the police. And in handling their task, the police must always respects and high appreciates on human right.